Factorial Analog of Distributive Bezout Domains - Zabavskii, B. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We investigate Bezout domains in which an arbitrary maximally-nonprincipal right ideal is two-sided. In the case of At(R) Bezout domains, we show that an arbitrary maximally-nonprincipal two-sided right ideal is also a maximally-nonprincipal left ideal.